Identification of phosphate transporter NaPi2b as MX35 cancer antigen by modified SEREX approach - Kiyamova, R.G.; Gryshkova, V.S.; Usenko, V.S.; Khozaenko, Y.S.; Gurtovyy, V.A.; Yin, B.; Ritter, G.; Old, L.; Gout, I.T.; Filonenko, V.V. (Біополімери і клітина, 2008)
In this study we describe the identification of sodium-dependent phosphate transporter NaPi2b as MX35 cancer-associated antigen. To achieve this goal we have screened extensively a cDNA expressing library from ovarian cancer cell line OVCAR3 with monoclonal antibody MX35. To further confirm the authenticity of this finding, we showed that bacterially and baculovirally expressed NaPi2b is specifically recognized by MX35 antibody. Moreover, the validity of these results was verified in a parallel study involving affinity purification and mass spectrometry. The epitope for MX35 monoclonal antibody was mapped to the largest extracellular loop of NaPi2b. Taken together, this study uncovers the identity of MX35 antigen and provides molecular tools for studying its function in normal and cancer tissues.